Eksistensi Tokoh Sulis dalam Novel Dunia Sunyi Karya Achi TM - Talitha Lulu Kharisma; Eggy Fajar Andalas (Faculty of Languages and Arts, Universitas Negeri Padang, 2022)
The study examined the novel of the silent world by achi tm by using the feminine theory of existentialism and female concept of image. Feminism existentialism is a stream of feminists that trivialize the existential problems of women. This study is included in a descriptive type of research. Data-collection techniques using note-reading techniques. The note-reading technique involves a reoccurring book of the silent world by achi tm to retrace the events that occurred as research data and are used to analyze. As for those data analysis techniques are as follows. 1) reviewing the data already collected, 2) regrouping data according to the issue of female image and female form of struggle in the private and public sphere, 3) interpreting data with existing theories, 4) concluding the findings. Research shows that the novel of the silent world by achi tm shows the image and struggle of the female figure, among other things: (1) the image of women is depicted physically by body and psyche and by virtue of abstinence, faithfulness, weakness, patience, and forgiveness; (2) the existence of a female figure is found through the struggle of a female figure in a good private and public domain.